(untitled) (PerCursos, 2022)
This text aims to discuss how the school addresses the child’s image rights, in order to reflect positively on the records of the works of the students of the Pedagogy course in the internship schools, being schools merged between private and public, from the Early Years, Child Education and some non-school spaces (Nursing Home, Driver Center, Education Secretary). We used the collection of documentary data carried out in observation reports from the year 2014 to 2019, from the supervised internship of the Pedagogy course, and above all to the data collected in the internship schools by the students of the course. We argue based on the results found that a change in attitudes regarding the use of the image of children in school is necessary, starting with important reflections on the subject in teacher training courses, aiming at a behavioral change that can protect the child in this sense, when we talk about pedagogical practice. In particular, a differentiated practice by the interns in their internship fields regarding the registration of the activities carried out.